A world review of fungi, yeasts, and slime molds in caves - Vanderwolf, Karen; Malloch, David; McAlpine, Donald; Forbes, Graham (International journal of speleology, 2013)
We provide a review of fungi, yeasts, and slime molds that have been found in natural solution caves and mines worldwide. Such habitats provide frequent roost sites for bats, and in eastern North America the environmental conditions that support white-nose syndrome, a lethal fungal disease currently devastating bat populations. A list of 1029 species of fungi, slime moulds, and yeasts in 518 genera have been documented from caves and mines worldwide in 225 articles. Ascomycota dominate the cave environment. Most research has been conducted in temperate climates, especially in Europe. A mean of 17.9 plus or minus 24.4SD fungal species are reported per study. Questions remain about the origin and ecological roles of fungi in caves, and which, if any, are cave-specialists. In the northern hemisphere, caves are generally characterized by relatively stable, low temperatures and a lack of organic substrates. This environment favors communities of oligotrophic, psychrotolerant fungi. Data that may help explain how cave environmental features and faunas influence the introduction and transmission of cave fungi remains scant.